Personal Skills Viewed from the Perspective of Medan Malay Culture - Mutiara, Mutiara; Nurhaliza, Siti; Priyanti, Adinda Sri; Lesmana, Gusman (Holistic Science, 2023)
The aim of this research is to describe the topic of self-efficacy as seen and assessed from the perspective of Malay cultural habits in the city of Medan. Self-sufficiency in life is a skill that is really needed by a person in order to be able to introduce himself well to many people. Behaviors included in personal skills are self-understanding or self-awareness and thinking skills. This is defined as a condition which is a skill that a person must have to have the courage to face life's problems and life naturally without feeling pressured, then proactively and creatively seek and find solutions so that they are able to overcome them. Even though knowing yourself is more of an attitude, it requires skills to realize it in daily behavior. Knowing oneself will encourage a person to worship according to his religion, be honest, work hard, be disciplined, be trustworthy, be tolerant of others, like to help and care for the environment. This article uses the literature method by collecting articles that explain the progress of the topic of human self-efficacy from various theories from various research according to field conditions.